On type 1 diabetes mellitus pathogenesis - Paschou, Stavroula A; Papadopoulou-Marketou, Nektaria; Chrousos, George P; Kanaka-Gantenbein, Christina (Endocrine Connections, 2018)
Type 1 diabetes mellitus (T1DM) results from the autoimmune destruction of β cells of the endocrine pancreas. Pathogenesis of T1DM is different from that of type 2 diabetes mellitus, where both insulin resistance and reduced secretion of insulin by the β cells play a synergistic role. We will present genetic, environmental and immunologic factors that destroy β cells of the endocrine pancreas and lead to insulin deficiency. The process of autoimmune destruction takes place in genetically susceptible individuals under the triggering effect of one or more environmental factors and usually progresses over a period of many months to years, during which period patients are asymptomatic and euglycemic, but positive for relevant autoantibodies. Symptomatic hyperglycemia and frank diabetes occur after a long latency period, which reflects the large percentage of β cells that need to be destroyed before overt diabetes become evident.